Functions of Circular RNAs in Regulating Adipogenesis of Mesenchymal Stem Cells - Fanglin Wang; Xiang Li; Zhiyuan Li; Shoushuai Wang; Jun Fan (Stem Cells International)
The mesenchymal stem cells (MSCs) are known as highly plastic stem cells and can differentiate into specialized tissues such as adipose tissue, osseous tissue, muscle tissue, and nervous tissue. The differentiation of mesenchymal stem cells is very important in regenerative medicine. Their differentiation process is regulated by signaling pathways of epigenetic, transcriptional, and posttranscriptional levels. Circular RNA (circRNA), a class of noncoding RNAs generated from protein-coding genes, plays a pivotal regulatory role in many biological processes. Accumulated studies have demonstrated that several circRNAs participate in the cell differentiation process of mesenchymal stem cells in vitro and in vivo. In the current review, characteristics and functions of circRNAs in stem cell differentiation will be discussed. The mechanism and key role of circRNAs in regulating mesenchymal stem cell differentiation, especially adipogenesis, will be reviewed and discussed. Understanding the roles of these circRNAs will present us with a more comprehensive signal path network of modulating stem cell differentiation and help us discover potential biomarkers and therapeutic targets in clinic.